The Homotopy Perturbation Method for Solving Some Types of Nonlocal Problems with Some Real Life Applications - Khaleel, Ahlam J (Al-Nahrain Journal of Science, 2012)
In this paper, we use the homotopy perturbation method for finding the solutions of the nonlocalproblems that consist of the one-dimensional heat equation together with nonlocal conditions andthe nonlocal problems that consist of the parabolic linear integro-differential equations togetherwith nonlocal conditions. Also, some numerical examples are presented to explain the efficiency ofthis method. Moreover, some real life applications for the nonlocal problems are solved via thismethod.